2019
DOI: 10.3390/su11216008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socio-Demographic Factors on Financial Sustainability of Public Services: A Comparative Analysis in Regional Governments and Local Governments

Abstract: In recent years, financial sustainability (FS) of public policies has become a key concept in all governmental levels due to the need for ensuring public services delivery for future generations. Prior research has been focused on the financial sustainability in local governments (LGs) although its findings suggested the need to analyze this magnitude in other levels of government because political decisions could be different in each type of public entity. So, FS has also become very relevant in the Regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Regarding the level of immigration, in model 3, the negative coefficient indicates an increase in social spending without contributing to it, influencing financial sustainability negatively. However, it has to be noted that, differently from other countries [30,48], demographic variables were not statistically significant.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Regarding the level of immigration, in model 3, the negative coefficient indicates an increase in social spending without contributing to it, influencing financial sustainability negatively. However, it has to be noted that, differently from other countries [30,48], demographic variables were not statistically significant.…”
Section: Resultsmentioning
confidence: 63%
“…The analysis revealed that in the Italian context the demographic variables did not influence the level of financial sustainability, unlike in other European countries [30,48]. Therefore, according to these results, the policymakers do not need to consider demographic factors in the management of financial sustainability.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For López-Subirés et al [6], the financial sustainability is a key dimension in the management of governmental organizations in many parts of the world, the monitoring of financial risk being one of the most important challenges to promote the transparency of local administration. Therefore, LG's managers and/or governments aim to find a fair and reliable model based on indicators to be able to measure the financial condition in order to achieve an alert system tool.…”
Section: Literature Reviewmentioning
confidence: 99%